The external elbow measure as surrogate of the anatomical width of cubital groove and possible risk factor of ulnar neuropathy at the elbow. (1st September 2020) - Mondelli, Mauro; Vinciguerra, Claudia; Lazzeretti, Stefano; Ciaramitaro, Palma; Sicurelli, Francesco; Greco, Giuseppe; Giorgi, Stefano; Aretini, Alessandro
Abstract: Introduction: There are no studies on elbow anthropometry in ulnar neuropathy at the elbow (UNE). We aimed to test the interrater agreement of external elbow measurements with caliper, the matching of external width of cubital groove (WCG) measures with those obtained through conventional radiography (XR) and ultrasonography (US). The final aim was to evaluate the differences of anthropometric elbow and body measures between UNE cases and controls with multicenter prospective study. Materials and methods: After common training of five observers for external elbow and body anthropometric measurements, we assessed the interrater agreement of measures in a single blind measurement session in 16 healthy volunteers. Then we verified if external WCG measures in eight and four of the above 16 subjects matched with those obtained with US and XR. Finally, we enrolled 40 consecutive idiopathic UNE cases in four electromyographic labs matched for sex and age with 40 controls to evaluate the differences of anthropometric measures. Results: There was high interrater agreement of all anthropometric body and elbow measures (Kendal's and interclass correlation coefficients between 0.84 and >0.9). We found high relations between WCG caliper measures and those obtained with US and XR ( r  > 0.9). WCG was smaller in cases than in controls (13.2 vs.15.7 mm, p  < 0.001). There were no differences in body anthropometric measures (BMI and waist-to-hip ratio). Conclusion: The external measurement of WCG is reliable and reproducible and may be risk factor of UNE. Future studies should be performed in lager samples evaluating the relations with lifestyle and occupational factors.